Using problem formulation for an efficient, fit-for-purpose risk assessment of microbial plant protection products - Anne K. Steenbergh; Gertie Arts; Peter A. H. M. Bakker; Wietse de Boer; Debora C. M. Glandorf; Mechteld M. S. ter Horst; Rob de Jonge; Willem Jan de Kogel; Jürgen Köhl (Environmental Sciences Europe)
Abstract The safety of the use of microbial plant protection products (PPP) is assessed before the products can be placed on the market. Due to large differences amongst microbial PPP a case-by-case approach is needed for this assessment. We propose to use the problem formulation approach based on pathways to harm to tailor the assessment to individual microbial PPP and to harmonise this approach when possible. The steps in problem formulation are described and examples are given of how the approach can be used for case-by-case assessments of microbial PPP. We also describe which other elements are needed to fully optimise the risk assessment of microbial PPP and how our approach fits in with the current EU regulatory framework and ongoing activities.